Rationale Behind an Optimal Field Experiment to Assess the Suitability of Soil Moisture Retrieval Algorithms for SAR Data - Barber, Matias Ernesto (2015)
Validation of soil moisture products derived from SAR remotely-sensed observations involves a comparison against ground-truth data. This validation step helps to state the performance of competing retrieval algorithms. Nevertheless, the design of a field experiment in the context of SAR retrieval is not straightforward. Ground-based measurements are affected by instrument errors due to both the physical limitations of the measurement technique and the uncertainties related to the spatial variability of the soil moisture. To properly assess the performance of the retrieved estimates both of the mentioned sources of uncertainties should be considered in the groundbased sampling and in the subsequent error assessment analysis. This paper addresses the rationale behind an optimal field experiment designed to assess the suitability of soil moisture retrieval algorithms.